2018
DOI: 10.1016/j.cej.2017.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Settleable engineered titanium dioxide nanomaterials for the removal of natural organic matter from drinking water

Abstract: Four linear engineered TiO 2 nanomaterials (LENs) were synthesized and evaluated in terms of settlability and their ability to remove natural organic matter (NOM) from river water. The size, surface characteristics, and crystallinity of the LENs were manipulated by varying the temperatures used during the synthesis procedure. All four LENs settled out of purified water more effectively than standard Degussa Evonik Aeroxide P25 nanoparticles. The settling behaviour of the nanomaterials was impacted by surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 37 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…26 Moreover, recent developments in nanotechnology have shown promising results for the application of engineered FeNPs in a series of environmental and industrial cleanup applications, such as drinking and wastewater treatment. 79…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Moreover, recent developments in nanotechnology have shown promising results for the application of engineered FeNPs in a series of environmental and industrial cleanup applications, such as drinking and wastewater treatment. 79…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of ions to the natural Fe-(hydr)­oxides of soils is a key process that regulates the bioavailability, toxicity, and mobility of specific nutrients and contaminants in the environment . Particularly, understanding the interaction between Fe-(hydr)­oxide nanoparticles (FeNPs) and oxyanions such as phosphate (PO 4 3– ), sulfate (SO 4 2– ), silicate (SiO 4 4– ), and arsenate (AsO 4 3– ) is of great relevance as its behavior varies under a wide range of environmental conditions. Moreover, recent developments in nanotechnology have shown promising results for the application of engineered FeNPs in a series of environmental and industrial cleanup applications, such as drinking and wastewater treatment. …”
Section: Introductionmentioning
confidence: 99%
“…Azar Fattahi et al found that the energy required for UV 254 removal of the system of LED with continuous irradiation of 405 nm, combined with P25 was 539.84 kW h/m 3 , which only showed little NOM removal rate [62]. Gora et al used TiO 2 nanobelts calcined at different temperatures and UVA-LED to degrade DOC in Otonabee River and Ottawa River water, whose maximum required energy reached 1085 kWh/m 3 [63,64]. Since the biochar/persulfate/ultrasonic system could achieve 90% removal rate for HAs within 60 min, the reaction time can be shortened according to the actual situation in order to reduce energy loss.…”
Section: Application Prospects In Real Water Treatment and The Reusab...mentioning
confidence: 99%
“…E EO is the energy in kWh needed to decrease the microcystin or TPA concentration by one order of magnitude in a liter of water. E EO was calculated by the following equations [40,41]:…”
Section: Electrical Energy Per Ordermentioning
confidence: 99%